2021
DOI: 10.3390/plants10102015
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Walled Carbon Nanotubes Improved Development during In Vitro Multiplication of Sugarcane (Saccharum spp.) in a Semi-Automated Bioreactor

Abstract: Carbon nanotubes play an important role in plant biotechnology due to their effects on the growth and differentiation of cells, tissues, organs, and whole plants. This study aimed to evaluate the effect of multi-walled carbon nanotubes (MWCNTs) during in vitro multiplication of sugarcane (Saccharum spp.) using a temporary immersion system. Morphological characterization of MWCNTs was carried out under a transmission electron microscope. Different concentrations (0, 50, 100, 200 mg L−1) of MWCNTs were added to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 37 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…One mechanism for the beneficial effects of MWCNTs has been their ability to promote the expression of genes involved in photosynthesis, thereby enhancing photosynthetic efficiency 56 . In addition, the increase in total chlorophyll content observed at low doses of MWCNTs/PVP (Table 4 ) may result from the increased photosynthetic activity 57 , 58 . Velikova et al 59 observed that SWCNTs could alter pea plants' leaf micromorphology and chloroplast ultrastructure, thereby affecting their photosynthetic activity.…”
Section: Discussionmentioning
confidence: 99%
“…One mechanism for the beneficial effects of MWCNTs has been their ability to promote the expression of genes involved in photosynthesis, thereby enhancing photosynthetic efficiency 56 . In addition, the increase in total chlorophyll content observed at low doses of MWCNTs/PVP (Table 4 ) may result from the increased photosynthetic activity 57 , 58 . Velikova et al 59 observed that SWCNTs could alter pea plants' leaf micromorphology and chloroplast ultrastructure, thereby affecting their photosynthetic activity.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that both nanoparticles showed a hormetic effect, characterized by stimulation at low doses and inhibition at high doses [5,40]. This study determined that the effective doses for the alleviation of PEG-induced WDS on camelina were 50-100 mg L −1 for MWCNTs and 5-10 mg L −1 for nano-Se, respectively.…”
Section: Discussionmentioning
confidence: 80%
“…MWCNTs act as effective plant-growth regulators that affect plant morpho-physiological and biochemistry [5]. They can penetrate the cell wall, enter the cytoplasm, and promote cell elongation in the root system, resulting in faster root growth and higher biomass production [49].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations